ELM control at the L → H transition by means of pellet pacing in the ASDEX Upgrade and JET all-metal-wall tokamaks. (April 2015) - Lang, P T; Meyer, H; Birkenmeier, G; Burckhart, A; Carvalho, I S; Delabie, E; Frassinetti, L; Huijsmans, G; Kocsis, G; Loarte, A; Maggi, C F; Maraschek, M; et al.
Abstract In ITER, pellets are used for ELM pacing and fueling. More importantly, ELM control and in particular control of the first ELM needs to be demonstrated in the non-nuclear phase of ITER during operation in H or He. Whilst D pellets have been established as an ELM control technique in the stationary phase with D target plasmas in devices with C as plasma-facing component, the behavior of other isotopes in non-stationary phases are not so well known. Here, we report on new pellet triggering experiments in ASDEX Upgrade and JET that mimic specific ITER operating scenarios. Both machines are equipped with an all-metal wall; recent investigations have shown that pellet triggering and pacing become more intricate when an all-metal wall surface is employed. In both machines, ELM triggering has been shown to occur after injection of D pellets into D plasmas during extended ELM-free phases, often following the L → H transition. In both devices the pellets are found to induce ELMs under conditions far from the stability boundary for type-I ELMs. Near the L → H transition, induced ELMs in some cases are more likely to have type-III rather than type-I characteristics. Furthermore, in ASDEX Upgrade this study was conducted during L → H transitions in the current ramp-up phase as envisaged for ITER. In addition, the pellet's ELM trigger potential has been proven in ASDEX Upgrade with a correct isotopic compilation for the non-nuclear phase in ITER, viz. H pellets into either He or H plasmas. Results from this study are encouraging since they have demonstrated the pellets' potential to provoke ELMs even under conditions that are quite far from the stability boundaries attributed to the occurrence of spontaneous ELMs. However, with the recent change from carbon to an all-metal plasma-facing component, examples have been found in both machines where pellets failed to establish ELM control under conditions where this would be expected and needed. Consequently, a major task of future investigations in this field will be to shed more light on the underlying physics of the pellet ELM triggering process to allow sound predictions for ITER.